A educação profissional e os fundamentos da escola unitária gramsciniana: o caso do Campus São João da Boa Vista do Instituto Federal de Educação, Ciência e Tecnologia de São Paulo - Gianelli, Juliana Gimenes (Universidade Federal de São Carlos, 2010)
In the new context of professional education entered in the federal system of vocational technology, we will investigate the professional education offered here on campus Sao Joao da Boa Vista Federal Institute of Education, Science and Technology of Sao Paulo. From the historical and dialectical materialism, we find that the institutional and government documents there are references to a unitary school of Gramsci and humanistic development, however, when we analyze the fundamentals that guide educational practices, we found the necessary elements to bring forth such a proposal education. In order to determine that the socioeconomic context of the region of Sao Joao justifies the provision of technical and technological courses Campus SBV before the logic of capitalism in this society today, we present the socioeconomic characteristics of the region, and we report data that reflect the origin social indicators of school and work-related activities, according to questionnaires completed by 265 students from Campus SBV. The report of empirical research revealed that the pedagogical courses come from the local and regional demand, and highlight the work as an educational principle with the relations between industry, technology and alienation of man in relation to work. Thus, we find that capitalist relations are present throughout the history of Brazilian professional education in such a way that indicated their social and economic consequences in the history of the Federal Institute of Sao Paulo. Given the current scenario of the new setting of professional education, due to a new government plan, we interpret the pedagogical institutional bias at the school gramscian unit, described in Book 12 in 1932. Therefore, we intend to demonstrate that the educational principle enunciated by Gramsci is necessary to develop technology education professional men omnilaterais from gramscian educational practices, such as the expansion of physical infrastructure, maintenance of the theoretical and practical , humanistic training for faculty and restructuring of the school curriculum. This allowed us to understand that school and creative unit is present in the school context which calls on its "selfless", aiming at moral and intellectual autonomy as well as the integrated development of human being.
Keywords: Educação profissional - história; Escola unitária; Tecnologia educacional; Homem omnilateral; Educação profissional tecnológica; Unitary school; Vocational education technology; Omnilateral man; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO